Application of Problem-Based Learning to Enhance Student Learning Outcomes in Basic Competencies of Maintaining Brake Systems - Cristian Emanuel Reinsini; I Wayan Susila; Mochammad Cholik; Tri Rijanto (Journal of Vocational Education Studies, 2021)
The purpose of this study was to determine the effect of the application of problem-based learning to improve student learning outcomes in the subject of Basic Competencies for Maintaining Brake Systems at SMK Negeri 2 Kupang. This study used a 2x2 factorial research design with experimental methods with a quantitative approach, consisting of two classes: the experimental and control classes. The control class is taught using a direct learning model, and the experimental class is taught using a problem-based learning model. The research sample was 70 students, 36 students from TKR 2 class (experiment class), and 34 students from class XI TKR 3 (control class). The instrument used consisted of a questionnaire of analytical skills, a test of learning outcomes in the cognitive domain, affective domain, and psychomotor domain. This study's results indicate that (1) student learning outcomes using problem-based learning models are significantly higher than learning outcomes for students who use the direct learning model; (2)Â  the learning outcomes of students who have high analytical skills are significantly higher than the learning outcomes of students who have low analytical skills; and (3) there is an interaction between the use of problem-based learning models and direct learning models on learning outcomes in the basic competency subject of the brake system at SMKN 2 Kupang.